2012
DOI: 10.4049/jimmunol.1201194
|View full text |Cite
|
Sign up to set email alerts
|

ICOS-Expressing CD4 T Cells Induced via TLR4 in the Nasal Mucosa Are Capable of Inhibiting Experimental Allergic Asthma

Abstract: Modulation of adaptive immune responses via the innate immune pattern recognition receptors, such as the TLRs, is an emerging strategy for vaccine development. We investigated whether nasal rather than intrapulmonary application of Protollin, a mucosal adjuvant composed of TLR2 and TLR4 ligands, is sufficient to elicit protection against murine allergic lower airway disease. Wild-type, Tlr2−/−, or Tlr4−/− BALB/c mice were sensitized to a birch pollen allergen extract (BPEx), then received either intranasal or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 65 publications
2
27
0
Order By: Relevance
“…For example, Foxp3 + CD4 + nTregs in humans are composed of populations with distinct cell surface display levels of ICOS (Ito et al 2008). Previous studies have shown that suppression of airway inflammation and AHR is associated with high levels of ICOS expression on CD4 + Tregs (Whitehead et al 2011) and that adoptive transfer of ICOS + CD4 + T cells, but not ICOS – cells, suppresses established AHR in mice (Shalaby et al 2012). We therefore compared numbers of ICOS + Foxp3 + Tregs, as well as the amount of ICOS on the cell surface of Tregs, in mice sensitized using 10 –3 or 10 –1 μg LPS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Foxp3 + CD4 + nTregs in humans are composed of populations with distinct cell surface display levels of ICOS (Ito et al 2008). Previous studies have shown that suppression of airway inflammation and AHR is associated with high levels of ICOS expression on CD4 + Tregs (Whitehead et al 2011) and that adoptive transfer of ICOS + CD4 + T cells, but not ICOS – cells, suppresses established AHR in mice (Shalaby et al 2012). We therefore compared numbers of ICOS + Foxp3 + Tregs, as well as the amount of ICOS on the cell surface of Tregs, in mice sensitized using 10 –3 or 10 –1 μg LPS.…”
Section: Resultsmentioning
confidence: 99%
“…Cell surface display levels of ICOS on Foxp3 + Tregs were also highest in mice sensitized using the suppressive dose of 10 –1 μg LPS. We did not directly compare the function of Tregs containing high and low levels of ICOS in the present study, but it has been previously observed that ICOS is required for suppression of allergic responses (Whitehead et al 2011) and that adoptive transfer of ICOS + CD4 + T cells suppresses airway eosinophilia and AHR, whereas transfer of ICOS – CD4 + T cells does not (Shalaby et al 2012). …”
Section: Discussionmentioning
confidence: 98%
“…Using mice eradicated of commensal bacteria, we also made the curious observation that re-establishing intestinal colonization with C. albicans alone does not induce ICOS expression by lamina propria CD4 + T cells. Whether this reflects discordant cell activation induced by C. ablicans compared with commensal enteric bacteria through TLR4 or NFAT that each promote CD4 + T-cell ICOS expression is uncertain, but represents an important area for future investigation (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, numerous studies showing a protective effect of microbial components against the development of allergic inflammation in murine models. For example, Toll-like receptor (TLR) 9 agonists inhibit the development of asthma-like inflammation [37,38], and intranasal administration of TLR2/4 ligands has been tested as a potential protective vaccine against allergic airway inflammation [39]. Protection may not be elicited through only microbial components.…”
Section: Noninfectious Microbesmentioning
confidence: 99%